Risks in human resources and their relation to organizational risk management : mitigating the HR risk of knowledge-loss, using knowledge management systems - Sigríður Gisela Stefánsdóttir 1989- (2017)
Allegedly, there is a positive relationship between HRM practices and the effectiveness and sustainable success of an organization. This relationship can only be positive when the employees, working for an organization, and the additional resources they bring to the operation are properly managed. Many organizations have human resource departments and most have risk management systems. It is important for organizations to manage all possible risks which might cause a halt in their operation, including the risks in relation to the human resources or so called HR risks. The purpose of the research is to see how medium-sized and larger knowledge-based organizations in Iceland are addressing and managing risks in human resources. This research puts a focus on the HR risk knowledge and aims to figure out if HR managers put enough value on knowledge, in knowledge-based organizations, to regard it as an HR risk and if they are systematically using knowledge management systems to try and mitigate the risk which could occur should they lose the knowledge. The research also raises the question whether HR risks should be included in organizations risk management system but such practices have become increasingly more common in other countries. The results indicate that HR managers are aware of risks in relation to human resources without being familiar with the term HR risks. They do realize that knowledge is an important component in their operation and are using various informal and formal practices to ensure the knowledge within doesn’t get lost. It is vital for organizations to realize which components are the major risk factors within to systematically work on mitigating them. If risk factors, such as knowledge-loss, are not systematically mitigated, organizations might lose their competitive advantage as well as their success in the market might decrease indefinitely. Sagt er að jákvætt samband sé milli þess að nota aðferðir mannauðsfræða og þess að ná fram skilvirkni og sjálfbærum árangri innan fyrirtækja. Þetta ...